Comparative study of mangrove recruitment in oil deforested areas in Guimaras, Philippines - Barnuevo, Abner P.
This study showed that mangroves has its way of recovering from perturbations as long as the geomorphological features of the habitats nat altered. The large scale mangrove plantingimplemented in Guimaras mangroves impacted by oil spill is deemed unnecessary since one year after the incident recruitment started to progress. Thus, future oil spill responses and interventions shouyld carefully assess first the natural recovery process of the initiatives and programs. Otherwise, the good intention of helping the fast recovery of mangroves and any other habitat impacted will just be a waste piblic funds and futile afforts vis-avis practically.